2007
DOI: 10.1016/j.neuropharm.2007.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain levels of neuropeptides in human chronic methamphetamine users

Abstract: SummaryAnimal data show that neuropeptide systems in the dopamine-rich brain areas of the striatum (caudate, putamen, and nucleus accumbens) are influenced by exposure to psychostimulants, suggesting that neuropeptides are involved in mediating aspects of behavioral responses to drugs of abuse. To establish in an exploratory study whether levels of neuropeptides are altered in brain of human methamphetamine users, we measured tissue concentrations of dynorphin, metenkephalin, neuropeptide Y, neurotensin, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Enhanced DYN immunoreactivity in the caudate and ventral pallidum but no changes in the putamen and prefrontal cortex of methamphetamine and cocaine users have been reported [295,296]. Methamphetamine users have decreased DYN immunoreactivity in the NAcc, medial pulvinar thalamic nucleus, and temporal/occipital association cortices [296]; changes not observed in cocaine users [295]. A significant correlation between recent psychostimulant use and PDYN expression in cingulate and dorsal lateral prefrontal cortices has also been reported [280].…”
Section: Dyn/kor System Alterations In Human Post-mortem Tissuementioning
confidence: 98%
See 1 more Smart Citation
“…Enhanced DYN immunoreactivity in the caudate and ventral pallidum but no changes in the putamen and prefrontal cortex of methamphetamine and cocaine users have been reported [295,296]. Methamphetamine users have decreased DYN immunoreactivity in the NAcc, medial pulvinar thalamic nucleus, and temporal/occipital association cortices [296]; changes not observed in cocaine users [295]. A significant correlation between recent psychostimulant use and PDYN expression in cingulate and dorsal lateral prefrontal cortices has also been reported [280].…”
Section: Dyn/kor System Alterations In Human Post-mortem Tissuementioning
confidence: 98%
“…PDYN expression is enhanced in putamen ''patches'' but not in caudate or NAcc of cocaine users, whereas [ 3 H]DYN binding is increased in the caudate relative to controls [277]. Enhanced DYN immunoreactivity in the caudate and ventral pallidum but no changes in the putamen and prefrontal cortex of methamphetamine and cocaine users have been reported [295,296]. Methamphetamine users have decreased DYN immunoreactivity in the NAcc, medial pulvinar thalamic nucleus, and temporal/occipital association cortices [296]; changes not observed in cocaine users [295].…”
Section: Dyn/kor System Alterations In Human Post-mortem Tissuementioning
confidence: 99%
“…Although mechanisms underlying D3 upregulation are still unclear, preclinical data suggest that it may result from repeated stimulation of D 1 receptors by dopamine during drug use, leading to the release of brain-derived neurotrophic factor (BDNF), which has, in turn, been linked to increased D 3 expression (Guillin et al, 2001) and was recently shown to be elevated in cocaine dependence in humans (D'Sa et al, 2011) (although it should be noted that no definite data support a causal role for BDNF in addiction, see (Pickens et al, 2011)). D 3 upregulation is thought to occur on GABAergic neurons containing D 1 receptors, substance P, and dynorphin (Frankel et al, 2008), as brain dynorphin concentrations are also elevated in human stimulant use (Frankel et al, 2007(Frankel et al, , 2008Kim et al, 2005). Inhibition of GABA neurons via increased transmission at D 3 could therefore modify the functional system responsible for the output of the limbic striatum, thereby modulating motivation to use drugs (see e.g.…”
Section: Evidence That the D 3 Receptor Is Upregulated In Animal Modementioning
confidence: 99%
“…Mass spectrometric approaches offer several advantages including higher sensitivity and throughput compared to traditional methods [16][17][18][19][20][21]. For example, recent neuropeptidomics studies have demonstrated high sensitivity characterization of peptides in diverse tissues such as human brain [22][23][24][25], and rat brain [26][27][28][29][30]. Moreover, several protocols for peptide characterization using mass spectrometry as analytical tools have been developed and are used routinely for biomedical applications [16,17,31,32].…”
Section: Introductionmentioning
confidence: 99%